The rewriting of the Homeric Hymn to Demeter in “Ira Demetrae” by Claribel Alegría - Fernández Zambudio, Josefa (Universidad Nacional de La Plata. Facultad de Humanidades y Ciencias de la Educación. Centro de Estudios Helénicos, 2020)
In this paper, we analyze Claribel Alegría’s poem “Ira Demetrae” as a renewal of the genre of hymns. We delimit its relationships with the account provided by Robert Graves in The Greek Myths, and we compare with ancient sources, especially the Homeric Hymn to Demeter, Hymn II of the Homeric Hymns collection, in order to find out the particularities and innovations of the rereading of Alegría. We specify the characters and contents chosen by the poet, and the images and details that she has used, as well as the objectives achieved. Further more, we contextualize this poem in the work of Claribel Alegría, looking for common topics. So, we offer a complete vision of the tradition that this poem renews, not studied until now.